2020
DOI: 10.12938/bmfh.2020-018
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from wild morels alters the spatial structure of gut microbiota and the production of short-chain fatty acids in mice

Abstract: Polysaccharides from morels possess many characteristics beneficial to health, such as anti-tumor and immunomodulatory activities. The gut microbiota plays a critical role in the modulation of immune function. However, the impact of morel polysaccharides on the gut microbiota has not yet been explored. In this study, a high-throughput pyrosequencing technique was used to investigate the effects of MP, a new heteropolysaccharide extracted from wild morels, on the diversity and composition of microbiota along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Bioactive compounds of morels mostly include polysaccharides, phenolics, tocopherols, and ergosterols (42)(43)(44)(45)(46)(47). Previous studies demonstrated that morels provided a wide range of health benefits not only due to the nutrient profile, but also the bioactive compounds (26,32,48).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioactive compounds of morels mostly include polysaccharides, phenolics, tocopherols, and ergosterols (42)(43)(44)(45)(46)(47). Previous studies demonstrated that morels provided a wide range of health benefits not only due to the nutrient profile, but also the bioactive compounds (26,32,48).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…As described above, some health-promoting effects including anti-cancer, gut health protection and immunoregulation are ascribed to polysaccharides (47,49,53). Therefore, the polysaccharides in morels can be potential functional ingredients that have wide applications on food, cosmetics, pharmaceutical preparations.…”
Section: Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal flora mainly depends on the intestinal nutrients to survive and participate in the metabolism of nutrients ( Guarner and Malagelada, 2003 ). Some polysaccharides and other ingredients in herbal medicine can be metabolized by bacteria into short-chain fatty acids (SFCA)( Rechkemmer et al, 1988 ; Huo et al, 2020 ), including butyric acid, acetic acid, propionic acid, etc. Among them, butyric acid is helpful for the repair of intestinal mucosa and the prognosis of sepsis.…”
Section: Herbal Medicine Gut Microbiota and Coronavirus Disease 19mentioning
confidence: 99%
“…The methanolic extract from the mushrooms has potent antioxidant properties and antibacterial activities against different bacteria [ 17 ]. It has been observed that the utilization of Morchella esculenta polysaccharides as a food in mice increased the useful gut microbiota as well as the short-chain fatty acids in the body [ 18 ]. A 43.6 kDa purified polysaccharide from M. esculenta was shown to contain glucose, mannose, galactose, and arabinose as the monomer units [ 19 ].…”
Section: Introductionmentioning
confidence: 99%